Dapagliflozin protects against nonalcoholic steatohepatitis in db/db mice - Qiao, Panshuang; Jia, Yingli; Ma, Ang; He, Jinzhao; Shao, Chen; Li, Xiaowei; Wang, Shuyuan; Yang, Baoxue; Zhou, Hong (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD), which is the most common liver disease, is associated with type 2 diabetes mellitus and the metabolic syndrome. Although there is no consensus on treatment of NAFLD, growing evidences suggest that tight glycemic control would contribute to the improvement of NAFLD. However, some insulin sensitizers can’t improve NAFLD, especially nonalcoholic steatohepatitis (NASH). Whether insulin independent hypoglycemic drug dapagliflozin, a sodium-glucose co-transporter-2 inhibitor, may improve NAFLD keeps unclear. Therefore, twelve-week-old male C57BL/6 wild-type and db/db mice were treated with 1 mg/kg dapagliflozin or vehicle for 12 weeks. Dapagliflozin alleviated NASH, manifesting as decreased alanine aminotransferase and NAFLD activity score in db/db mice. Hepatic triglycerides content was reduced by dapagliflozin through decreasing de novo lipogenesis via inhibiting FXR/SHP/ LXRα/SREBP-1c pathway and glucose output in the liver of db/db mice. Moreover, dapagliflozin treatment reduced inflammatory response through inhibiting NF-κB pathway, and alleviated fibrosis by restoring the balance between fibrogenesis and fibrolysis in the liver of db/db mice. In summary, dapagliflozin alleviates NASH mostly through reducing lipid accumulation, inflammation, and fibrosis. These findings provide new insights for understanding the protective effect of dapagliflozin in NASH and suggest that dapagliflozin may be used to treat NASH.